2022
DOI: 10.3390/bioengineering9110686
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on New Developed Titanium Alloys for Biomedical Applications

Abstract: The mechanical properties and electrochemical behavior of two new titanium alloys, Ti20Mo7Zr and Ti20Mo7Zr0.5Si, are investigated in this paper. The alloys have been manufactured by vacuum arc remelting (VAR) technique and studied to determine their microstructure, corrosion behavior, and mechanical properties. Metallographic observations and quantitative microanalysis by optical microscopy, scanning electron microscopy SEM, and energy dispersive X-rays spectroscopy EDX were performed. Data about the three-poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…There are other reports on biocompatible titanium alloys with a low Young’s modulus besides TiNbSn alloys [ 7 , 8 , 9 , 10 , 11 ]. TiNbSn alloys have been clinically applied in hip replacement stems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other reports on biocompatible titanium alloys with a low Young’s modulus besides TiNbSn alloys [ 7 , 8 , 9 , 10 , 11 ]. TiNbSn alloys have been clinically applied in hip replacement stems.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the difference in the Young’s moduli of implants and the human cortical bone leads to a disproportionate stress distribution, resulting in pain and bone atrophy after surgery [ 6 ]. To resolve this problem, new titanium alloys, such as TiMoZrTa, TiMoZrSi, and TiZrTaSn alloys, have been developed that possess a low Young’s modulus in combination with biocompatibility and strength, and they have shown excellent material properties and favorable results in preclinical studies have been reported [ 7 , 8 , 9 , 10 , 11 ]. In our institute, the development of a near-β-type TiNbSn alloy with a low Young’s modulus of <50 GPa was speculated to reduce stress shielding and thigh pain [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most implants are made of metallic biomaterials. The most commonly used metals for medical applications are titanium and titanium alloys as well as stainless steel and cobalt–chromium–molybdenum alloys [ 9 ]. For example, Ti6Al4V and NiTi alloys are known for their high wear resistance, ductility and high hardness.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of chloride ions (Cl − ) or proteins that act as electrolytes and lead to a low oxygen content in the body fluid could initiate and support the corrosive process. This contributes to a lower or greater extent to the release of these toxic elements, and when they accumulate in significant quantities, they can cause allergenic or even carcinogenic effects [ 8 , 9 , 10 , 11 , 12 , 13 ]. To avoid these undesirable aspects, many researchers have published studies on new types of titanium-based alloys, which replaced the problematic elements with others that can lead to the same characteristic properties, and developed alloys with a low Young’s modulus with β or near β phase [ 2 , 6 , 12 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elements, such as Niobium, Tantalum, Zirconium, Molybdenum, and Tungsten form beta phases with Titanium, which then form different alloy systems that overcome the toxicity associated with Ti-6Al-4V alloys—Ti-Nb-Zr, Ti-Nb-Zr-Sn, Ti-Nb-Ta-Zr, Ti-Mo-Si, Ti-Mo-Zr-Ta, Ti-Mo-Zr-Fe [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In [ 13 ], two new titanium alloys—Ti20Mo7Zr and Ti20Mo7Zr0.5Si—were studied in terms of mechanical characteristics and electrochemical behavior. The electrochemical studies were carried out in a simulated body fluid (SBF) and saline medium, and the conditions for fever were even simulated.…”
Section: Introductionmentioning
confidence: 99%